Peran Kepuasan Dan Motivasi Pengunjung Terhadap Niat Berkunjung Kembali Ke Taman Satwa Taru Jurug - Shalli Habiibika Baaq; Sarah Fadila; Esti Dwi Rahmawati; Haris Novy Admadianto (Pusat Riset dan Inovasi Nasional, 2022)
Tourism is a very important sector in supporting economic development in Indonesia. The existing potential, natural resources, historical and cultural heritage can be developed into attractive leading tourist destinations that encourage tourists to make repeat visits to the same destinations. One of them is the Taru Jurug Animal Park in Surakarta City, Central Java. The purpose of this study was to analyze the role of visitor satisfaction and motivation on the intention to return to the same destination. The method used in this research is descriptive quantitative with a survey method for all tourists visiting Taru Jurug Surakarta Animal Park using a questionnaire. And using convenience sampling technique, with a total of 100 respondents. Then the data were analyzed using multiple linear regression analysis using SPSS.